Polarization resolved four-wave-mixing-based measurement in bulk material semiconductor optical amplifier - Bradley, Louise (My University, 2006)
The anticipated growth in demand for bandwidth leads to the development of all-optical signal processing techniques at ever increasing data rates. One possible candidate to achieve the required performance is the semiconductor optical amplifier (SOA). It has been demonstrated that ultra-fast gain processes are dominant for pulsewidths below 10 ps. In this paper we present experimental results on the polarization dependence of ultra-fast gain dynamics in InGaAsP/InP bulk material SOA probed using a four-wave mixing technique. Using a standard low-pass filter model it is possible to retrieve information on the polarization dependence of linewidth enhancement factors and the timescales for non-linear phenomena such as carrier density pulsation and carrier heating
International Conference on Transparent Optical Networks
PUBLISHED
INVITED
Keywords: semiconductor; SOA